Idee geografiche per educare al mondo - GIORDA, Cristiano; ZANOLIN, GIACOMO (Tratti geografici - Open Access, 2020)
This book aims to contribute to the renewal of geographic education and the teaching of geography. Traditional methods of teaching geography are becoming increasingly obsolete. Hence the need to take new paths in search of alternatives to convey the ideas of which geography is the bearer. The Italian Association of Geography Teachers (AIIG) is committed to a continuous effort aimed at reiterating the importance of geography in school curricula and more generally in the education of citizens aware of their role in the world and responsible in their actions on it.